Characterisation of extended-spectrum b-lactamases among Klebsiella pneumoniae isolates causing bacteraemia and urinary tract infection in Mozambique - Pons, Maria J. (2015)
The aim of this study was to determine the prevalence of extended-spectrum b-lactamase (ESBL)- producing Klebsiella pneumoniae isolated from urinary tract and bloodstream infections in a rural hospital in Manhic¸a, Mozambique. ESBLs were investigated among ceftriaxone-non-susceptible K. pneumoniae clinical isolates recovered between 2004 and 2009. Characterisation of blaCTX-M, blaSHV, blaOXA and blaTEM genes was performed by PCR and sequencing. Epidemiological relationships were established by phylogenetic analysis, repetitive extragenic palindromic PCR (REP-PCR), pulsed-field gel electrophoresis (PFGE) and multilocus sequence typing (MLST), whilst plasmid transferability was evaluated by conjugation. In addition,the presence of class 1 and 2 integrons was studied.A total of 19 K. pneumoniae were analysed. The blaCTX-M-15 gene was found in all strains. Other ESBL genes were found concomitantly, including blaSHV-5, blaSHV-2, blaSHV-2A, blaSHV-12 and blaSHV-38. In addition, other b-lactamases such as blaTEM-1 and blaOXA-30 were also detected. REP-PCR identified 15 different epidemiological profiles. MLST analysis also showed great variability of sequence types. The blaCTX-M-15 gene showed a high transfer capacity. The presence of class 1 integrons was high. High levels of multidrug resistance were also found. In conclusion, these data show the dominance of the CTX-M-type ESBL, particularly CTX-M-15, supporting its worldwide dissemination, including in areas with limited access to third-generation cephalosporins. This finding is a matter of concern for clinical management as third-generation cephalosporins are an alternative for treating severe cases of multidrug-resistant infections in this community.